Electrode mixture sheet, electrode, secondary battery, and method for manufacturing electrode mixture sheet
By reasonably preparing PTFE, carbon materials and other fluororesins in the electrode mix sheet, controlling the distribution of carbon materials and the PTFE fiber morphology, the problem of difficult to take into account the tensile strength and conductivity of the electrode mix sheet in the battery is solved, and high energy density and good cycling stability are achieved.
Patent Information
- Application Number
- JP2024095891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-06-13
- Filing Date
- 2024-06-13
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2044-06-13
AI Technical Summary
In the existing battery technology, it is difficult to balance the tensile strength and conductivity of the electrode hybrid heet, resulting in insufficient energy density and cyclic stability of the battery.
By rationally formulating polytetrafluoroethylene (PTFE), carbon materials and other fluororesins in the electrode mix sheet, the carbon material distribution and the morphology of PTFE fibers are controlled, thereby optimizing the mechanical and electrical properties of the electrode mix sheet.
The high tensile strength and low resistance of the electrode hybrid sheet are achieved, which improves the energy density and cycle stability of the battery.
Smart Images

Figure 0007659216000005 
Figure 0007659216000006 
Figure 0007659216000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode mixture sheet, an electrode, a secondary battery, and a method for manufacturing an electrode mixture sheet. [Background technology]
[0002] Secondary batteries such as lithium-ion secondary batteries are used in small, portable electric and electronic devices such as notebook computers, mobile phones, smartphones, tablet computers, and ultrabooks, due to their high voltage, high energy density, low self-discharge, low memory effect, and the ability to be made extremely lightweight, and are also being put into practical use as a wide range of power sources, including on-board power sources for driving automobiles and large stationary power sources. There is a demand for secondary batteries to have even higher energy density, and further improvements in their battery characteristics are required.
[0003] Patent Document 1 describes an electrode in which the distribution of polytetrafluoroethylene in the electrode mixture is controlled. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2022 / 163186 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide an electrode mixture sheet having high tensile strength and low resistance, an electrode and a secondary battery using the same, and a method for manufacturing the electrode mixture sheet. [Means for solving the problem]
[0006] The present disclosure (1) includes polytetrafluoroethylene, a carbon material, and an electrode active material other than the carbon material and / or a fluororesin other than the polytetrafluoroethylene, In an image of the carbon composition distribution obtained by SEM-EDX analysis with a magnification of 2000 times, the value X shown by the interface length / detected amount of carbon is 2300 or less.
[0007] The present disclosure (2) is the electrode mixture sheet according to the present disclosure (1), in which the value X is 300 or more and 2000 or less.
[0008] The present disclosure (3) is an electrode mixture sheet according to the present disclosure (1) or (2), in which the total content of the polytetrafluoroethylene and the fluororesin other than polytetrafluoroethylene in the electrode mixture sheet is 0.1 mass% or more and 10 mass% or less.
[0009] The present disclosure (4) is an electrode mixture sheet according to any one of the present disclosures (1) to (3), in which the carbon material is a conductive assistant.
[0010] The present disclosure (5) is an electrode mixture sheet according to any one of the present disclosures (1) to (4), in which the electrode active material other than the carbon material is a positive electrode active material.
[0011] The present disclosure (6) is the electrode mixture sheet according to the present disclosure (5), in which the content of the positive electrode active material is 92% or more and 99% or less by mass with respect to the electrode mixture sheet.
[0012] The present disclosure (7) is an electrode including the electrode mixture sheet according to any one of the present disclosures (1) to (6).
[0013] The present disclosure (8) is a secondary battery including the electrode according to the present disclosure (7).
[0014] The present disclosure (9) relates to a process (1) for mixing polytetrafluoroethylene with an electrode active material other than a carbon material and / or a fluororesin other than the polytetrafluoroethylene; Step (2) of mixing the mixture obtained in step (1) with a carbon material. The method for producing an electrode mixture sheet includes the steps of:
[0015] The present disclosure (10) relates to the production method according to the present disclosure (9), in which fibrils of the polytetrafluoroethylene are generated by shear force in the step (1).
[0016] The present disclosure (11) relates to the production method according to the present disclosure (9) or (10), in which the mixing in step (2) is performed under a lower shear force than in step (1).
[0017] The present disclosure (12) is the production method according to any one of the present disclosures (9) to (11), in which all of the components mixed in step (1) are powders, and step (1) is carried out in the absence of a liquid medium.
[0018] The present disclosure (13) is the production method according to any one of the present disclosures (9) to (12), in which the treatment temperature in the step (2) is lower than the treatment temperature in the step (1).
[0019] The present disclosure (14) is the production method according to any one of the present disclosures (9) to (13), in which the steps (1) and (2) are carried out using the same apparatus. Effect of the Invention
[0020] According to the present disclosure, it is possible to provide an electrode mixture sheet having high tensile strength and low resistance, an electrode and a secondary battery using the same, and a method for manufacturing an electrode mixture sheet. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing an example of spectrum data obtained by SEM-EDX analysis. [Diagram 2] FIG. 2 is a diagram showing an example of an image of a carbon composition distribution of an electrode mixture sheet obtained by SEM-EDX analysis at a magnification of 2000 times. [Diagram 3] FIG. 2 is a diagram showing an example of an image obtained by binarizing an image obtained by SEM-EDX analysis. [Figure 4] FIG. 13 is a diagram illustrating a method for calculating an interface length. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present disclosure will now be described in detail.
[0023] The present disclosure provides an electrode mixture sheet that includes polytetrafluoroethylene (PTFE), a carbon material, and an electrode active material other than the carbon material and / or a fluororesin other than the PTFE, and in an image of a carbon composition distribution obtained by SEM-EDX analysis with a magnification of 2000, a value X indicated by interface length / detected amount of carbon is 2300 or less.
[0024] In the electrode mixture sheet of the present disclosure, the tensile strength of the electrode mixture sheet can be improved and the resistance can be suppressed by setting the value X to 2300 or less. This is believed to be because the dispersion state and shape of the PTFE fibrils located around the carbon material are appropriately controlled. In terms of achieving higher tensile strength and lower resistance, the value X is preferably 2000 or less, more preferably 1800 or less, even more preferably 1500 or less, even more preferably 1300 or less, and is preferably 300 or more, more preferably 450 or more, and even more preferably 750 or more.
[0025] The value X is calculated as follows. <Measurement sample> The electrode mixture sheet is cut into a size of 1 cm x 1 cm (thickness is optional) to prepare a measurement sample. When preparing a measurement sample from an electrode, the surface containing the electrode mixture is cut into the above size to prepare a measurement sample. <Interface length (pix)> (i) For each measurement sample, three images of the carbon composition distribution are obtained using SEM-EDX (scanning electron microscope-energy dispersive X-ray spectroscopy) analysis with a 2000x field of view, an acceleration voltage of 3000V, and an image size of 1280 x 960. For example, the first image is obtained from the center of the measurement sample, and the second and third images are obtained from points shifted 2 mm to the left and right from the center of the measurement sample. For example, an SU8000 manufactured by Hitachi High-Tech Corporation can be used to obtain the images. (ii) The images obtained in (i) are binarized. Images obtained with N=3 per sample are divided into brightness levels of 0 to 255 for each image, and a threshold is obtained for each image using Otsu's binarization method. After that, the average value of the binarization thresholds for each image is calculated, and the average threshold value for the samples is calculated. Using the average threshold value, each pre-binarization image is binarized again. The Otsu binarization method is a method for calculating a binarization threshold value in which the point at which the degree of separation between two peaks obtained when a gray-scale histogram is drawn is the highest is set as the brightness threshold value. (iii) In the images obtained in (ii), the number of elements whose inter-pixel element differences are not 0 is counted, and the resulting value is regarded as the interface length of each image. <Detected carbon amount (cps / eV)> The amount of carbon detected for each image is calculated from the spectrum data obtained simultaneously with the image data (i) above. The spectrum data used is the spectrum data obtained when measuring with SEM-EDX, with the horizontal axis being X-ray energy [keV] and the vertical axis being X-ray intensity [cps / eV]. Figure 1 shows an example of the spectrum data. From the spectrum data, the maximum value on the vertical axis of the peak appearing near 0.27 keV, which is the specific energy of carbon, is read, and the value read is regarded as the amount of carbon detected. <Interface length ÷ detected carbon amount (value X)> From the interface length and carbon detection amount calculated for each image, the interface length ÷ carbon detection amount is calculated for three points for each sample, and the average value of N=3 is used as the interface length ÷ carbon detection amount (value X) for each sample.
[0026] The method of calculating the interface length will be specifically described with reference to the drawings. FIG. 2 shows an example of an image of the carbon composition distribution of an electrode mixture sheet obtained by SEM-EDX analysis at a magnification of 2000 times. By binarizing the image in FIG. 2 using the method described above, the image in FIG. 3 is obtained. In this binarized image, the number of elements whose inter-pixel difference is not 0 is counted and regarded as the interface length. Here, the difference in elements between pixels is not 0 means that the colors (white or black) of adjacent pixels (squares) are different, as shown in Figure 4. Sides (sides indicated by diagonal lines in the figure) that are in contact with pixels of different colors are counted as elements in which the difference in elements between pixels is not 0. In Figure 4, the number of such elements is 21, and the interface length is 21.
[0027] The electrode mixture sheet of the present disclosure contains PTFE. The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed of only TFE units and modified monomer units. As the PTFE, the modified PTFE is preferred in that it improves the binding force, sheet strength and flexibility.
[0028] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving the binding force, sheet strength, and flexibility. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and even more preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, even more preferably 0.50% by mass, even more preferably 0.40% by mass, and even more preferably 0.30% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.
[0029] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0030] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.
[0031] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf 1 (A) (In the formula, Rf 1 represents a perfluoro organic group. ) and the like. In this specification, the above-mentioned "perfluoro organic group" means an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.
[0032] The perfluorovinyl ether may, for example, be a compound represented by the general formula (A) in which Rf 1 and perfluoro(alkyl vinyl ether) [PAVE], which is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.
[0033] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.
[0034] The perfluorovinyl ether further includes, in the above general formula (A), Rf 1 is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, Rf 1 is the following formula:
[0035] [ka]
[0036] (wherein m represents 0 or an integer of 1 to 4), Rf 1 is the following formula:
[0037] [ka]
[0038] (wherein n represents an integer of 1 to 4).
[0039] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.
[0040] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 2 (B) (In the formula, Rf 2 represents a perfluoro organic group.
[0041] Above Rf 2 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.
[0042] As the modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the composite sheet, at least one selected from the group consisting of PAVE, HFP, VDF, and CTFE is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) [PMVE], HFP, VDF, and CTFE is more preferable.
[0043] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-A-2005-527652 may be used.
[0044] Examples of PTFE that are commonly available on the market include F-104, F-106, F-107, F-104C, F-121, F-201, F-205, F-208, and F-302 manufactured by Daikin Industries, 60X, 601X, 602X, 605XTX, 613AX, 62X, 62NX, 62XTX, 640XTX, 641XTX, 650XTX, 669X, 669NX, 6CX, 6CNX, CFP6000X, 6J, 6CJ, 62J, 640J, and 641J manufactured by Chemours, and 3M. Examples of such compounds include TF2029, TF2025Z, TF2053Z, TF2073Z, TF2001Z, TF2071USZ, and TF2072Z, as well as CD145, CD123, CD126E, CD097, CD084E, CD086EL, CD086EH, CD090E, CD122E, CD141E, and CD127E manufactured by AGC Corporation, and DF681F, DF680F, DF330F, DF291F, DF230F, DF210F, DF132F, DF130F, and DF120F manufactured by Solvay.
[0045] In terms of being able to form a composite sheet having even greater strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.
[0046] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.
[0047] The above PTFE preferably has a standard specific gravity (SSG) of 2.280 or less, more preferably 2.250 or less, even more preferably 2.220 or less, even more preferably 2.200 or less, even more preferably 2.190 or less, especially preferably 2.180 or less, and particularly preferably 2.170 or less. The SSG is also preferably equal to or greater than 2.130. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895 89.
[0048] In the electrode mixture sheet of the present disclosure, it is preferable that at least a portion of the PTFE is fibrillated.
[0049] The PTFE content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more, relative to the electrode mixture sheet, and is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0050] The electrode mixture sheet of the present disclosure contains a carbon material. Examples of the carbon material include a conductive assistant, a carbon-based negative electrode active material, etc. Among these, the conductive assistant is preferable. The content of the carbon material in the electrode mixture sheet is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, and is preferably 99% by mass or less, more preferably 96% by mass or less, and even more preferably 92% by mass or less.
[0051] The conductive assistant is not particularly limited, but examples thereof include graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF. These may be used alone or in any combination and ratio of two or more.
[0052] The content of the conductive assistant relative to the electrode mixture sheet is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 15% by mass or less, and even more preferably 5% by mass or less.
[0053] Examples of the carbon-based negative electrode active material include any one selected from artificial graphite, graphite carbon fiber, resin-calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon, or a mixture of two or more thereof.
[0054] The content of the carbon-based negative electrode active material is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 75% by mass or more, relative to the electrode mixture sheet, and is preferably 99% by mass or less, more preferably 96% by mass or less, and even more preferably 92% by mass or less.
[0055] The electrode mixture sheet of the present disclosure contains an electrode active material other than the above carbon material and / or a fluororesin other than the above PTFE (hereinafter also referred to as other fluororesin). The content of the electrode active material other than the carbon material and / or the fluororesin other than the PTFE is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, and even more preferably 1 mass% or more, relative to the electrode mixture sheet, and is preferably 99 mass% or less, more preferably 96 mass% or less, and even more preferably 92 mass% or less.
[0056] Examples of the electrode active material other than the carbon material include a positive electrode active material and a negative electrode active material other than carbon. Among these, a positive electrode active material is preferable.
[0057] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.
[0058] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge) and alkali metal-cobalt composite oxides (lithium-cobalt composite oxides, etc.). In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.
[0059] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co 0.15 Al 0.05 O2 or MNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 and the like are preferred, and a compound represented by the following general formula is preferred. MNi h Co i Mn j M 5 k O2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.
[0060] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO4) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li. That is, the alkali metal-containing transition metal phosphate compound is preferably a lithium-containing transition metal phosphate compound.
[0061] The transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound is preferably one having an olivine structure.
[0062] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.
[0063] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 A positive electrode active material such as O2 is preferable because the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or more. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the above-mentioned positive electrode active material is preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.
[0064] Other positive electrode active materials include M2MnO3 and MM 6O2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.). Examples also include solid solution materials with O2.
[0065] As the above solid solution material, for example, an alkali metal manganese oxide represented by the general formula Mx[Mn (1-y) M 7 y O z can be mentioned. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn. For example, it contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, a manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O2 is preferable because it can provide an alkali metal ion secondary battery having a high energy density.
[0066] In addition, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferably used by mixing with the above positive electrode active material. The amount of lithium phosphate used is preferably at least 0.1% by mass, more preferably at least 0.3% by mass, still more preferably at least 0.5% by mass, and preferably at most 10% by mass, more preferably at most 8% by mass, still more preferably at most 5% by mass, based on the total of the above positive electrode active material and lithium phosphate.
[0067] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.
[0068] The above positive electrode active materials may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.
[0069] The content of the positive electrode active material in the electrode mixture sheet is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 75% by mass or more, and most preferably 92% by mass or more, and is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less.
[0070] Examples of negative electrode active materials other than the carbon-based materials include lithium metal, silicon and silicon-containing compounds such as silicon alloys, Li4Ti5O 12 and the like, or a mixture of two or more kinds thereof.
[0071] The above-mentioned non-carbon-based negative electrode active materials preferably contain silicon as a constituent element, which allows a high-capacity battery to be produced.
[0072] The silicon-containing material is preferably silicon particles, particles having a structure in which fine silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≦x≦1.6), or a mixture thereof. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a high capacity, and excellent cycle characteristics can be obtained.
[0073] Silicon oxide in the present disclosure is a general term for amorphous silicon oxide, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≦x≦1.6). x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, which is then cooled and precipitated.
[0074] The content of the negative electrode active material other than the carbon material is preferably 1 mass% or more, more preferably 2 mass% or more, even more preferably 5 mass% or more, particularly preferably 8 mass% or more, relative to the electrode mixture sheet, and is preferably 97 mass% or less, more preferably 90 mass% or less, and even more preferably 80 mass% or less.
[0075] The other fluororesin may be a PTFE different from the PTFE as the essential component described above (hereinafter, also referred to as other PTFE), a melt-processable fluororesin, etc. The other PTFE is preferable in that it can provide a higher tensile strength and a lower resistance.
[0076] The other PTFE may be PTFE having a composition and / or physical properties different from those of the PTFE as the essential component described above.
[0077] Examples of PTFEs having different compositions include PTFEs having different types of modifying monomers copolymerizable with tetrafluoroethylene (TFE) and / or different contents of polymerized units (modifying monomer units) based on the modifying monomers.
[0078] The combination of the essential component PTFE and the PTFE with different composition may be, for example, a combination of a homopolymer of TFE and a modified PTFE, a combination of two or more modified PTFEs with different types of modified monomers, or a combination of two or more PTFEs having the same modified monomer unit but with different content ratios of the modified monomer unit. "Different content ratios of modified monomer units" means that the difference in the content ratios (mass% value) of the modified monomer units in all polymerized units is 0.005 or more. The difference in the content ratios is preferably 0.10 or more, more preferably 0.15 or more, even more preferably 0.20 or more, and is preferably 0.80 or less, more preferably 0.60 or less, and even more preferably 0.40 or less.
[0079] As the above combination, a combination of a homopolymer of tetrafluoroethylene (TFE) and modified PTFE is particularly preferable.
[0080] The homopolymer of TFE refers to one in which the content of modified monomer units relative to the total polymerized units is less than 0.0001% by mass.
[0081] The modified PTFE as the PTFE having a different composition may be the same as the modified PTFE described above as the PTFE as the essential component.
[0082] The other PTFE may be a PTFE having a different standard specific gravity (SSG) from the PTFE as the essential component. "Different SSG" means that the difference in SSG is 0.005 or more. The difference in SSG is preferably 0.010 or more, more preferably 0.015 or more, even more preferably 0.020 or more, and is preferably 0.050 or less, more preferably 0.040 or less, and even more preferably 0.030 or less.
[0083] The other PTFE may be a PTFE having a different extrusion pressure from the PTFE as the essential component. "Different extrusion pressure" means that the difference in extrusion pressure is 5 MPa or more. The difference in extrusion pressure is preferably 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more, and is preferably 35 MPa or less, more preferably 30 MPa or less, and even more preferably 25 MPa or less. The extrusion pressure is measured by the following method. In the latter half of the extrusion operation in the paste extrusion described below, the load (N) when the pressure reaches an equilibrium state is divided by the cross-sectional area of the cylinder to obtain the extrusion pressure (MPa). (Paste Extrusion) 60 g of PTFE powder and 12.3 g of hydrocarbon oil (trade name: Isopar G (registered trademark), manufactured by ExxonMobil Corporation) as an extrusion aid are mixed in a polyethylene container for 3 minutes. The above mixture is filled into the cylinder of an extruder at room temperature (25±2°C), and a load of 0.47 MPa is applied to the piston inserted into the cylinder and held for 1 minute. The mixture is then extruded from an orifice at a ram speed of 20 mm / min. The ratio of the cross-sectional area of the cylinder to the cross-sectional area of the orifice is 200.
[0084] Examples of the melt-processable fluororesin include tetrafluoroethylene [TFE] / perfluoro(alkyl vinyl ether) [PAVE] copolymer [PFA], TFE / hexafluoropropylene [HFP] copolymer [FEP], ethylene [Et] / TFE copolymer [ETFE], Et / TFE / HFP copolymer [EFEP], polychlorotrifluoroethylene [PCTFE], chlorotrifluoroethylene [CTFE] / TFE copolymer, CTFE / TFE / PAVE copolymer, Et / CTFE copolymer, polyvinyl fluoride [PVF], polyvinylidene fluoride [PVdF], vinylidene fluoride [VdF] / TFE copolymer, VdF / HFP copolymer, VdF / TFE / HFP copolymer, VdF / HFP / (meth)acrylic acid copolymer, VdF / CTFE copolymer, VdF / pentafluoropropylene copolymer, VdF / PAVE / TFE copolymer, and TFE / perfluoroalkyl allyl ether copolymer. The above perfluoroalkyl allyl ether is CF2=CFCF2-O-Rf 3 (Rf 3 is a monomer represented by a perfluoroalkyl group having 1 to 5 carbon atoms. Of these, polyvinylidene fluoride [PVdF] is preferred.
[0085] As used herein, melt processable means that the polymer is capable of being melted and processed using conventional processing equipment such as extruders and injection molders. The melt-processable fluororesin preferably has a melt flow rate (MFR) of 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more, and preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less. In this specification, MFR is a value obtained in accordance with ASTM D1238 using a melt indexer as the mass (g / 10 min) of polymer flowing out per 10 min from a nozzle with an inner diameter of 2 mm and a length of 8 mm at a measurement temperature (e.g., 372°C for PFA and FEP, and 297°C for ETFE) determined depending on the type of fluoropolymer and a load (e.g., 5 kg for PFA, FEP, and ETFE).
[0086] The mass ratio of PTFE as the essential component to the other fluororesin (PTFE / other fluororesin) is preferably 1 / 99 or more, more preferably 5 / 95 or more, even more preferably 10 / 90 or more, even more preferably 15 / 85 or more, and particularly preferably 20 / 80 or more, and is preferably 99 / 1 or less, more preferably 95 / 5 or less, even more preferably 90 / 10 or less, even more preferably 85 / 15 or less, and particularly preferably 80 / 20 or less.
[0087] The total content of PTFE as the essential components and the other fluororesins is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.5 mass% or more, relative to the electrode mixture sheet, and is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 3 mass% or less.
[0088] The electrode mixture sheet of the present disclosure particularly preferably contains PTFE, a carbon material as a conductive assistant, and a positive electrode active material. The electrode mixture sheet may be a positive electrode mixture sheet. The PTFE, conductive assistant, and positive electrode active material in this embodiment may be the above-mentioned ones. The PTFE content in the above embodiment is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.5 mass% or more, relative to the electrode mixture sheet, and is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 3 mass% or less. The content of the carbon material (conductive assistant) in the above embodiment is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, and even more preferably 1 mass % or more, relative to the electrode mixture sheet, and is preferably 30 mass % or less, more preferably 15 mass % or less, and even more preferably 5 mass % or less. The content of the positive electrode active material in the above embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 75% by mass or more, relative to the electrode mixture sheet, and is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less.
[0089] In the electrode mixture sheet of the present disclosure, the PTFE as the essential component and the other fluororesin (if present) act as binders, but may further contain other binders. Examples of the other binder include, but are not limited to, resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; thermoplastic elastomeric polymers such as EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-styrene copolymer, and styrene-isoprene-styrene block copolymers or hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, and propylene-α-olefin copolymer; and polymer compositions having ionic conductivity for alkali metal ions (particularly lithium ions). These may be used alone or in any combination of two or more in any ratio.
[0090] The content of the other binder is usually 0.01 to 3% by mass with respect to the electrode mixture sheet.
[0091] The electrode mixture sheet of the present disclosure may further include a solid electrolyte. That is, the electrode mixture sheet of the present disclosure may be an electrode mixture sheet for a solid battery including an electrode active material and a solid electrolyte.
[0092] The solid electrolyte may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, there is an advantage that the flexibility of the sheet is improved.
[0093] The sulfide-based solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(X=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12 Any one selected from the above, or a mixture of two or more of them, can be used.
[0094] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in that the electrochemical device has a high energy density.
[0095] The oxide-based solid electrolyte is preferably a compound that contains an oxygen atom (O), has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation properties.
[0096] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12, LiPO (4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 (LLZ) and others. Ceramic materials in which elements have been substituted for LLZ are also known. For example, Li 6.24 La3Zr2Al 0.24 O 11.98 , Li 6.25 Al 0.25 La3Zr2O 12 and Li substituted with Ta 6.6 La3Zr 1.6 Ta 0.4 O 12 , Li substituted with Nb 6.75 La3Zr 1.75 Nb 0.25 O 12 Other examples include LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) is substituted for LLZ. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON, LiPOD, in which part of the oxygen in lithium phosphate is substituted with nitrogen, etc. 1 (D 1is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.
[0097] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0098] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the NASICON type is preferred.
[0099] The volume average particle diameter of the oxide-based solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, and more preferably 0.03 μm or more. The upper limit is preferably 100 μm or less, and more preferably 50 μm or less. The average particle diameter of the oxide-based solid electrolyte particles is measured by the following procedure. The oxide-based solid electrolyte particles are diluted and adjusted to a 1 mass% dispersion in a 20 ml sample bottle using water (heptane in the case of a substance unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasonic waves for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is taken 50 times using a laser diffraction / scattering type particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C using a measurement quartz cell to obtain the volume average particle diameter. For other detailed conditions, etc., refer to the description of JISZ8828:2013 "Particle size analysis - dynamic light scattering method" as necessary. Five samples are prepared for each level and the average value is adopted.
[0100] The content of the solid electrolyte in the electrode mixture sheet is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less.
[0101] The electrode mixture sheet of the present disclosure has a thickness of preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, particularly preferably 150 μm or less, and preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.
[0102] The electrode mixture sheet of the present disclosure has a tensile strength of 0.10 N / mm 2 It is preferable that the resistance is 0.15N / mm or more. 2 More preferably, it is 0.20 N / mm 2 More preferably, it is 0.25 N / mm 2 More preferably, it is 0.30 N / mm2 More preferably, it is 1.5 N / mm 2 may be less than or equal to 1.0 N / mm 2 It may be the following. The tensile strength is measured by the following method. The electrode mixture sheet is cut out to prepare a 4 mm wide rectangular test piece. A tensile tester (Shimadzu Corporation AGS-100NX) is used to measure at 100 mm / min. The chuck distance is 40 mm. Displacement is applied until breakage occurs, and the maximum stress of the measured results is taken as the tensile strength.
[0103] The electrode mixture sheet of the present disclosure preferably has a resistance value of less than 200 Ω·cm, more preferably less than 150 Ω·cm, even more preferably 100 Ω·cm or less, even more preferably 80 Ω·cm or less, particularly preferably 50 Ω·cm or less, and may be 0.1 Ω·cm or more. The resistance value is measured by the following method. The surface resistivity (Ω / □) of the electrode mixture layer is measured using a four-terminal four-probe method (Mitsubishi Chemical Analytech: Loresta GP (MCP-T610)). After measurement, the surface resistivity is multiplied by the thickness of the mixture layer to obtain the volume resistivity (Ω·cm) of the electrode mixture sheet. The thickness of the mixture layer is measured at three points on the electrode mixture sheet using a microgauge, and the average value is used.
[0104] The electrode mixture sheet of the present disclosure can be obtained, for example, by a manufacturing method for an electrode mixture sheet including a step (1) of mixing PTFE with an electrode active material other than a carbon material and / or a fluororesin other than the PTFE (another fluororesin), and a step (2) of mixing the mixture obtained in the step (1) with a carbon material. The present disclosure also relates to such a method of manufacture. It is believed that adding the carbon material later reduces damage to the carbon material caused by shear forces that generate fibrils, making it less likely that the conductive paths will be damaged and reducing resistance.
[0105] The PTFE, the electrode active material other than the carbon material, and the other fluororesin in the above step (1) are the same as those described in the electrode mixture sheet of the present disclosure. When a solid electrolyte is used, it is preferable to mix it in step (1). The components mixed in step (1) above are preferably in the form of powder. In the above step (1), it is preferable not to mix a carbon material.
[0106] The above step (1) is preferably carried out in the absence of a liquid medium.
[0107] Examples of the mixing method in the above step (1) include a method of mixing using a single-shaft kneader, a twin-shaft kneader, a mix muller, a high-speed stirring mixer, a planetary mixer, a jet mill, etc. In the above step (1), the mixing conditions may be appropriately set to the rotation speed and mixing time. For example, the rotation speed is preferably 10,000 rpm or less. It is preferably 500 rpm or more, more preferably 1,000 rpm or more, and even more preferably 1,500 rpm or more, and also preferably 8,000 rpm or less, more preferably 6,000 rpm or less, and even more preferably 5,000 rpm or less. If it is below the above range, it will take a long time to mix, which will have a negative effect on productivity. If it exceeds the above range, fibrillation will proceed excessively, and there is a risk of an electrode mixture sheet having poor strength and flexibility. For example, the mixing time is preferably 60 minutes or less. It is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 3 minutes or more, and also preferably 30 minutes or less, more preferably 20 minutes or less, and even more preferably 10 minutes or less.
[0108] In the above step (1), it is preferable to generate fibrils of the PTFE by shearing force.
[0109] In the above step (1), the treatment temperature may be appropriately set. For example, the treatment temperature is preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower, and is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher.
[0110] In the above step (1), the materials may be mixed and then molded into a bulk shape. Specific methods for molding into a bulk shape include extrusion molding, press molding, and the like. In addition, the "bulk shape" does not specify a particular shape, and may be in the form of a single mass, and includes shapes such as rods, sheets, spheres, and cubes.
[0111] In the above production method, after the end of step (1), it is preferable not to newly add any electrode active material other than the carbon material and any other fluororesin.
[0112] In the above step (2), the mixture obtained in the above step (1) is mixed with a carbon material. In this manner, by mixing the carbon material after the electrode active material other than the carbon material and the other fluororesin, the value X can be easily adjusted to within the above range, and an electrode mixture sheet having high tensile strength and low resistance can be produced.
[0113] The carbon material in the above step (2) is the same as that described in the electrode mixture sheet of the present disclosure.
[0114] The above step (2) is preferably carried out in the absence of a liquid medium.
[0115] The mixing method in the above step (2) includes, in addition to the mixing method in the above step (1), a mixing method using a W-type mixer, a V-type mixer, a drum-type mixer, a ribbon mixer, a conical screw-type mixer, etc.
[0116] The mixing in the step (2) is preferably performed with a lower shear force than that in the step (1). By mixing in this manner, the value X can be more easily adjusted to fall within the above-mentioned range, and an electrode mixture sheet having higher tensile strength and lower resistance can be produced. The shear force in step (2) can be adjusted to a range lower than that in step (1) by using an apparatus capable of applying a lower shear force than that in step (1) or by setting any one or more of the processing time, the rotation speed of the apparatus, the input amount, and the processing temperature lower than those in step (1).
[0117] In the above step (2), the mixing conditions may be any conditions capable of applying a shear force lower than that in the above step (1), and a processing device having a mechanism that does not apply a strong shear force, such as a W-type mixer, a V-type mixer, a drum-type mixer, a ribbon mixer, a conical screw-type mixer, etc. Also, in the processing device that can be used in the above step (1), by setting any one or more of the processing time, rotation speed, input amount, and processing temperature lower than those in the above step (1), the materials can be mixed and dispersed while weakening the shear force. The processing time is preferably shorter than that of the above step (1), and is preferably 0.9 times or less, more preferably 0.8 times or less, even more preferably 0.6 times or less, and is preferably 0.1 times or more, more preferably 0.2 times or more, even more preferably 0.3 times or more, based on the above step (1). The rotation speed is preferably lower than that in step (1) above, and is preferably 0.9 times or less, more preferably 0.8 times or less, even more preferably 0.7 times or less, and is preferably 0.01 times or more, more preferably 0.05 times or more, even more preferably 0.1 times or more, and even more preferably 0.2 times or more, based on the rotation speed in step (1) above. The amount of the compound added is preferably less than that in step (1) above, and is preferably 0.9 times or less, more preferably 0.8 times or less, even more preferably 0.6 times or less, and is preferably 0.2 times or more, more preferably 0.3 times or more, even more preferably 0.4 times or more, based on the amount of the compound added in step (1) above. The treatment temperature is preferably lower than that in the above step (1), and is preferably at most 10°C lower, more preferably at most 20°C lower, even more preferably at most 30°C lower, and is preferably at least 200°C lower, more preferably at least 150°C lower, even more preferably at least 100°C lower, based on the above step (1). It is preferable that the step (2) is carried out using the same apparatus as that used in the step (1), and it is particularly preferable that the same apparatus as that used in the step (1) is used, but with different rotation speed and processing time.
[0118] The above-mentioned production method preferably further comprises a step (3) of rolling the electrode mixture obtained in the above-mentioned step (2) into a sheet shape.
[0119] Specific examples of the rolling method in the above step (3) include rolling methods using a roll press, a plate press, a calendar roll machine, or the like. Among these, a roll press machine in which metal rolls are arranged opposite to each other, and a calender roll machine in which a plurality of metal rolls are further arranged are preferable. In this case, it is preferable that there is a speed difference between the pair of metal rolls. The transport speed of the downstream roll is preferably 1.1 times or more, more preferably 1.3 times or more, and even more preferably 1.5 times or more, based on the transport speed of the upstream roll. Although there is no particular upper limit, it is preferable that the upstream roll is moved at a low speed without being stopped.
[0120] After the above step (3), a step (4) may be carried out in which a larger load is applied to the obtained rolled sheet to roll it into a thinner sheet, or step (4) may be carried out repeatedly. In this way, the flexibility of the rolled sheet is improved by rolling it little by little in stages, rather than thinning it all at once. The number of times of step (4) is preferably 2 to 10 times, and more preferably 3 to 9 times. Specific rolling methods include, for example, a method in which two or more rolls are rotated and the rolled sheet is passed between them to process it into a thinner sheet. In the above steps (3) and (4), the treatment temperature may be appropriately set. For example, the treatment temperature is preferably 250° C. or less, more preferably 200° C. or less, and even more preferably 180° C. or less, and is preferably 30° C. or more, more preferably 40° C. or more, and even more preferably 50° C. or more. Heating the material makes it flexible and improves its workability.
[0121] The electrode mixture sheet of the present disclosure can be used as an electrode mixture sheet for a secondary battery. It can be used for either a negative electrode or a positive electrode. In particular, the electrode mixture sheet is suitable for a lithium ion secondary battery.
[0122] The present disclosure also provides an electrode comprising the electrode mixture sheet of the present disclosure. The electrode of the present disclosure has high tensile strength and low resistance.
[0123] The electrode of the present disclosure may include the above-described electrode mixture sheet of the present disclosure and a current collector.
[0124] The electrodes of the present disclosure may be positive electrodes or negative electrodes.
[0125] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.
[0126] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.
[0127] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.
[0128] The positive electrode may be manufactured by a conventional method, for example, a method in which an electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.
[0129] The density of the positive electrode mixture sheet is preferably 2.80 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.
[0130] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.
[0131] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.
[0132] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.
[0133] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.
[0134] The present disclosure also provides a secondary battery comprising the electrode of the present disclosure described above.
[0135] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.
[0136] The secondary battery using the above-mentioned electrolyte may use electrolytes, separators, etc. that are used in known secondary batteries. These will be described in detail below.
[0137] The electrolyte is preferably a non-aqueous electrolyte, which may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.
[0138] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.
[0139] The electrolyte salt may be a lithium salt, such as LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, or LiN(SO2C2F5)2, and is preferably LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or a combination thereof, because of its excellent cycle characteristics.
[0140] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more, and the upper limit is usually 2.0 mol / L or less, although it depends on the organic solvent for dissolving the electrolyte salt.
[0141] The secondary battery using the above-mentioned electrolyte preferably further includes a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.
[0142] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.
[0143] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.
[0144] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.
[0145] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fibrillated resin as a binder.
[0146] The material of the exterior case is not particularly limited as long as it is a material that is stable against the electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate films are preferably used.
[0147] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.
[0148] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.
[0149] The solid-state secondary battery is preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based all-solid-state secondary battery.
[0150] The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.
[0151] The solid electrolyte used in the solid electrolyte layer may be the same as the solid electrolyte that can be used in the electrode mixture sheet of the present disclosure described above.
[0152] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.
[0153] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.
[0154] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.
[0155] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES
[0156] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.
[0157] PTFE-1 to PTFE-2 were prepared and analyzed by the following method.
[0158] <Average primary particle diameter> The PTFE aqueous dispersion was diluted with water until the solid content became 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average primary particle diameter determined by measuring the unidirectional diameter using a transmission electron microscope were measured to prepare a calibration curve. Using this calibration curve, the average primary particle diameter was determined from the measured transmittance of the 550 nm projected light for each sample.
[0159] <Polymer solids concentration> 1 g of the aqueous PTFE dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass (1 g) of the aqueous dispersion was expressed as a percentage and used.
[0160] <Modified monomer content> The CTFE content was determined by producing a thin film disk by press molding the PTFE powder or composition, and measuring the infrared absorbance of the thin film disk using FT-IR. -1 Absorbance at / 2360cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at
[0161] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.
[0162] A white solid A was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.
[0163] Preparation example 1 In a 6-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 3480 g of deionized water, 100 g of paraffin wax, and 5.3 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 15.0 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 400 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached about 1200 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 310 nm, and the solid content concentration was 25.3 mass%.
[0164] The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the mixture was filtered to separate the water, thereby obtaining a wet PTFE powder. The resulting wet PTFE powder was dried at 180° C. for 18 hours to obtain PTFE-1. The SSG of the obtained PTFE-1 was 2.156.
[0165] Example 2 In a 6-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 80 ° C. to remove oxygen. After adding 1.20 g of CTFE, TFE was further injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 80 ° C. while stirring. Next, an aqueous solution of 360 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 10 mg of ammonium persulfate dissolved in 20 g of water were injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 80 ° C. and the system pressure at 0.78 MPaG. When 1530 g of TFE was consumed from the start of polymerization (conversion rate 90%), 4.2 g of CTFE was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached about 1700 g from the start of polymerization, the stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 241 nm, and the solid content was 32.0 mass%.
[0166] The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the mixture was vigorously stirred in a vessel equipped with a stirrer to cause solidification, and then filtered to separate the water, thereby obtaining a wet PTFE powder. The resulting wet PTFE powder was dried at 145°C for 18 hours to obtain PTFE-2. The CTFE content of the obtained PTFE-2 was 0.23 mass %, and the SSG was 2.170.
[0167] The mixture sheets of the examples and comparative examples were prepared and evaluated according to the following procedures. The composition ratios were adjusted to the values shown in Table 1. (Preparation of electrode mixture sheet) Example 1 [Process 1] The positive electrode active material A and PTFE-1 were weighed and thoroughly heated in a thermostatic bath at 60° C. Then, they were placed in a high-speed stirring mixer and stirred for 1 minute at a blade rotation speed of 6850 rpm to apply shear force, resulting in a mixture in which many fibrils were generated. [Process 2] After cooling to 25° C., the conductive assistant AB was added as a carbon material to the obtained mixture, and the mixture was processed at 1500 rpm for 1 minute to disperse the carbon material in the mixture, thereby obtaining an electrode mixture. [Process 3] The electrode mixture was fed into a rolling machine capable of rotating at different peripheral speeds to obtain an electrode mixture sheet (temperature: 60° C., left roll rotation speed: 1 m / min, right roll rotation speed: 0.8 m / min). [Step 4] The obtained mixture sheet was similarly placed in the rolling machine again and rolled to obtain an electrode mixture sheet having greater sheet strength. Thereafter, the electrode mixture sheet was placed in a roll press machine and the gap was adjusted to a final thickness of 80 μm.
[0168] Example 2 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 1900 rpm, and the treatment time was changed to 3 minutes.
[0169] Example 3 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 4,300 rpm, and the treatment time was changed to 3 minutes.
[0170] Example 4 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1.
[0171] Example 5 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 3000 rpm, and the treatment time was changed to 10 minutes.
[0172] Example 6 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 3000 rpm, and the treatment time was changed to 20 minutes.
[0173] Example 7 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1 and the treatment time in [Step 1] was changed to 3 minutes.
[0174] Example 8 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1 and the treatment time in [Step 1] was changed to 3 minutes.
[0175] Example 9 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 4,300 rpm, and the treatment time was changed to 3 minutes.
[0176] Example 10 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1 and the treatment time in [Step 1] was changed to 3 minutes.
[0177] Example 11 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the rotation speed in [Step 1] was changed to 1500 rpm, and the treatment time was changed to 10 minutes.
[0178] Example 12 A composite sheet was prepared in the same manner as in Example 1, except that in [Step 1], silicon oxide was used as the active material other than carbon, the amount of PTFE-1 was 1 mass %, the amount of PTFE-2 was 1 mass %, and the treatment time was 3 minutes, and in [Step 2], graphite was used as the carbon material.
[0179] Example 13 A mixture sheet was produced in the same manner as in Example 1, except that the material composition was changed to that shown in Table 1, the treatment time in [Step 1] was changed to 3 minutes, and the treatment temperature in [Step 3] was changed to 140°C.
[0180] Comparative Example 1 [Process 1] The positive electrode active material A, PTFE-1, and conductive additive AB as a carbon material were weighed and thoroughly heated in a thermostatic bath at 60°C. After that, they were put into a high-speed stirring mixer and stirred for 1 minute at a blade rotation speed of 6850 rpm to apply shear force, resulting in a mixture with many fibrils. [Process 2] After cooling to 25° C., the resulting mixture was processed at 1500 rpm for 1 minute to obtain an electrode mixture. [Step 3] and [Step 4] were carried out in the same manner as in Example 1 to prepare a mixture sheet.
[0181] (How to check for the occurrence of fibrils) The mixture after [Step 1] was observed under an SEM (magnification: 7000x) to confirm the generation of fibrils. In Examples 1 to 12, it was possible to observe the appearance of a plurality of fibrils generated from the PTFE.
[0182] (Measurement of value X) <Measurement sample> The electrode mixture sheet was cut into a size of 1 cm x 1 cm (thickness can be chosen as desired) to prepare a measurement sample. <Interface length (pix)> (i) For each measurement sample, three images of the carbon composition distribution were taken using SEM-EDX (scanning electron microscope-energy dispersive X-ray spectroscopy) analysis with a 2000x field of view, an acceleration voltage of 3000V, and an image size of 1280 x 960. The first image was taken at the center of the measurement sample, and the second and third images were taken at points shifted 2 mm to the left and right from the center of the measurement sample. The images were taken using a Hitachi High-Tech SU8000. (ii) The images obtained in (i) were subjected to binarization processing. Images obtained with N=3 per sample were divided into brightness levels of 0 to 255 for each image, and a threshold was obtained for each image using Otsu's binarization method. After that, the average value of the binarization thresholds for each image was calculated, and the average threshold for the sample was calculated. Using the average threshold, each pre-binarization image was binarized again. (iii) In the images obtained in (ii), the number of elements whose inter-pixel difference was not 0 was counted, and the resulting value was regarded as the interface length of each image. <Detected carbon amount (cps / eV)> The amount of carbon detected in each image was calculated from the spectrum data obtained simultaneously with the image data (i) above. The spectrum data used was the spectrum data obtained by measuring with SEM-EDX, with the horizontal axis being X-ray energy [keV] and the vertical axis being X-ray intensity [cps / eV]. From the spectrum data, the maximum value on the vertical axis of the peak appearing near 0.27 keV, which is the specific energy of carbon, was read, and the value read was taken as the amount of carbon detected. <Interface length ÷ detected carbon amount (value X)> From the interface length and carbon detection amount calculated for each image, the interface length ÷ carbon detection amount was calculated for three points for each sample, and the average value of N=3 was used as the interface length ÷ carbon detection amount (value X) for each sample. The results are shown in Table 2.
[0183] (Measurement of the strength of electrode mixture sheets) The electrode mixture sheet was cut out to prepare a 4 mm wide rectangular test piece. A tensile tester (Shimadzu Corporation AGS-100NX) was used to measure at 100 mm / min. The chuck distance was 40 mm. Displacement was applied until breakage, and the maximum stress of the measurement results was taken as the strength of each sample. The results are shown in Table 2.
[0184] (Measurement of resistance of electrode mixture sheet) The electrode mixture sheet was cut into a 5 cm square sample, and the surface resistivity (Ω / □) of the mixture layer was measured using a four-terminal four-probe method (Mitsubishi Chemical Analytech: Loresta GP (MCP-T610)). After measurement, the surface resistivity was multiplied by the thickness of the mixture layer to obtain the volume resistivity (Ω·cm) of the electrode mixture sheet. The thickness of the mixture layer was measured at three points on the electrode mixture sheet using a microgauge, and the average value was used. The measured volume resistivity was evaluated as follows. A: Less than 100Ωcm B: 100Ωcm or more to less than 150Ωcm C: 150Ωcm to less than 200Ωcm D:200Ωcm or more The results are shown in Table 2.
[0185] [Table 1]
[0186] [Table 2]
[0187] The abbreviations in the table are as follows. Cathode active material A: Li(Ni 0.6 Mn 0.2 Co 0.2 )O2 Cathode active material B: Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 AB: Denka acetylene black Li-100 SuperP Li: Carbon black manufactured by Imerys PVdF-1: Modified PVdF with acrylic acid functional groups (D50 = 2.0 μm)
Claims
1. An electrode mixture sheet comprising polytetrafluoroethylene, a carbon material, and an electrode active material other than the carbon material and / or a fluororesin other than the polytetrafluoroethylene, The content of the polytetrafluoroethylene is 0.1% by mass or more relative to the electrode mixture sheet, An electrode mixture sheet in which a value X, which is indicated by interface length / detected amount of carbon, is 2300 or less in an image of a carbon composition distribution obtained by SEM-EDX analysis with a magnification of 2000 times.
2. 2. The electrode mixture sheet according to claim 1, wherein the value X is 300 or more and 2,000 or less.
3. 3. The electrode mixture sheet according to claim 1, wherein a total content of the polytetrafluoroethylene and the fluororesin other than polytetrafluoroethylene in the electrode mixture sheet is 0.1% by mass or more and 10% by mass or less.
4. 3. The electrode mixture sheet according to claim 1, wherein the carbon material is a conductive assistant.
5. 3. The electrode mixture sheet according to claim 1, wherein the electrode active material other than the carbon material is a positive electrode active material.
6. 6. The electrode mixture sheet according to claim 5, wherein the content of the positive electrode active material is 92% or more and 99% or less by mass based on the electrode mixture sheet.
7. An electrode comprising the electrode mixture sheet according to claim 1 or 2.
8. A secondary battery comprising the electrode according to claim 7.
9. A step (1) of mixing polytetrafluoroethylene with an electrode active material other than a carbon material and / or a fluororesin other than the polytetrafluoroethylene; and Step (2) of mixing the mixture obtained in step (1) with a carbon material. Including, A method for producing an electrode mixture sheet, wherein all of the components mixed in step (1) are powders, and step (1) is carried out in the absence of a liquid medium.
10. The method according to claim 9, wherein in the step (1), fibrils of the polytetrafluoroethylene are generated by a shear force.
11. The method according to claim 9 or 10, wherein the mixing in step (2) is carried out under a lower shear force than that in step (1).
12. The method according to claim 9 or 10, wherein the treatment temperature in the step (2) is lower than the treatment temperature in the step (1).
13. The method according to claim 9 or 10, wherein the steps (1) and (2) are carried out using the same apparatus.
Citation Information
Patent Citations
Positive mix paste for lithium secondary battery
JP2010097817A
Mixture slurry and production method thereof, and electrode and battery using the mixture slurry
JP2014194927A
Electrodes for low-resistance electrochemical elements, methods for manufacturing the same, and electrochemical elements including the electrodes
JP2015532519A
Pre-wetting dry electrode for secondary battery, manufacturing method thereof, and secondary battery comprising the same
KR1020220093603A
Electrode and electrode manufacturing method
WO2022163186A1